Affirmation Policy Formulation in the Field of Staffing in Meeting the Need to Create Quality Employees - Lily Bauw (Faculty of Law, Musamus University, 2022)
The granting of Special Autonomy is to realize justice, uphold the rule of law, implement human rights (HAM), accelerate economic development, improve the welfare and progress of the Papuan people in order to realize and balance the progress of other provinces. The purpose of this study was to determine and analyze the Affirmation Policy in the field of employment in meeting the needs of qualified employees. The method used is normative legal research to be able to solve problems by examining secondary data. Secondary data is obtained by studying and reviewing library materials in the form of legal materials, both primary legal materials, secondary legal materials, and tertiary legal materials. presented descriptively. The results of this study are the need for a clear and responsible juridical basis in the implementation of special regional staffing fields, namely by making special Provincial regulations and Regency Regional Regulations.